N′‐Formyl‐2‐(5‐nitrothiophen‐2‐yl)benzothiazole‐6‐carbohydrazide as a potential anti‐tumour agent for prostate cancer in experimental studies. (16th November 2012) - Rodrigues, Juan R.; Charris, Jaime; Camacho, José; Barazarte, Arthur; Gamboa, Neira; Nitzsche, Bianca; Höpfner, Michael; Lein, Michael; Jung, Klaus; Abramjuk, Claudia
Abstract: Objectives: Benzothiazoles (BZTs) represent organic compounds with different biological actions. In this study we aimed to investigate ten newly synthesized BZT derivatives as potential anti‐tumour agents against prostate cancer in vitro and in vivo . Methods: The cytotoxic effect of these compounds was screened on the human prostate cancer cell lines PC‐3 and LNCaP. The most effective compound, N ′‐formyl‐2‐(5‐nitrothiophen‐2‐yl)benzothiazole‐6‐carbohydrazide, was further characterized regarding its dose‐ and time‐dependent effects on cell viability and proliferation (XTT test) as well as on adhesion and spreading (real‐time cell analyzer xCelligence), migration (scratch‐wound repair assay) and invasion (Boyden chamber) of the cells. This BZT derivative was also tested as an inhibitor of angiogenesis (chicken chorioallantoic membrane assay), clonogenic activity (soft agar) and matrix metalloproteinase 9 (gelatin zymography). Key findings: N ′‐Formyl‐2‐(5‐nitrothiophen‐2‐yl)benzothiazole‐6‐carbohydrazide significantly inhibited all tested properties of the prostate cancer cell lines and showed low toxic in vitro and in vivo effects. The in vitro anti‐tumour activity of this compound was confirmed by the in vivo effects on PC‐3 xenografts in nude mice. Tumour growth was decreased in treated compared with untreated mice. Conclusions: These results suggest the potential capacity of BZTs and in particular N ′‐formyl‐2‐(5‐nitrothiophen‐2‐yl)benzothiazole‐6‐carbohydrazide as anti‐tumour agents for the treatment of prostate cancer.